Artificial Intelligence in Service Quality Improvement: A Bibliometric Analysis - Nurkholish Majid; Ahmad Khumaeni; Hewa Majeed Zangana (Universitas Airlangga, 2026)
Background: Advances in computer technology have enabled the development of machines with capabilities known as Artificial Intelligence (AI). Although its adoption in manufacturing industries remains limited in many countries, AI is increasingly being applied in the service sector and other industries. Objective: This study aims to map recent research trends on the use of AI in improving service quality. Method: The data were analyzed using bibliometric mapping with VOSviewer software, focusing on studies about AI in services and service quality over the past five years. Results: This study maps the use of AI in corporate service automation. AI enables consumer self-service through robotic systems, particularly in sectors such as hospitality, lodging, travel, and tourism. Furthermore, the adoption of AI services by companies helps reveal patterns in consumer behavior. The keyword analysis identified five main clusters: medical, agriculture, government, tourism, and service quality. Conclusion: AI contributes to the enhancement of automation-based systems in sectors such as tourism and travel. However, AI use also faces challenges across sectors, including medical, business services, agriculture, hospitality, and government or public services. Keywords: Artificial Intelligence, Service Quality